AN INVESTIGATION INTO CONTRACTORS’ EVALUATION OF RISKS ASSOCIATED WITH THE JBCC PRINCIPAL BUILDING AGREEMENT IN SOUTH AFRICA - Ayman Othman; Nishani Harinarain (Journal of Construction Project Management and Innovation)
Construction is a risky business, and risk management is an essential responsibility in managing construction projects and organisations. Hence, construction contracts have been developed to organise the relationship between project participants and manage associated risks. This paper provides an investigation into the contractors’ responses and feedback obtained through the application of an innovative framework developed by the authors towards identifying, quantifying and classifying the risks associated with the Joint Building Contractors Committee Principal Building Agreement Series 2000 (JBCC PBA) in South Africa. Qualitative and quantitative techniques have been used in this study for data collection and analysis. Purposive sampling was adopted to identify the respondents, and 9 construction managers were interviewed. The interviews were structured so that they were carried out in a free and unbiased manner and responding contractors were asked to complete a questionnaire. Analysis of responses showed that the developed Identification, Quantification and Classification Framework (IQCF) is an innovative and accepted tool that is able to fill the gap in managing project risks and will complement current practices. It is seen to be of benefit to firms in assisting with training of employees and helping junior employees understands and uses the JBCC (PBA). Investigating the validity and reliability of the developed framework is of prime importance to ensure its suitability to manage risks associated with the JBCC (PBA). For this reason contractor’s responses and feedback are based on the practical application of the framework which ultimately increases its value and contribution to the construction industry. The adoption and application of the framework will enable contractors to enhance the risk-management process in South Africa.